2016
DOI: 10.1089/cbr.2016.2132
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Importance of Bone Marrow Uptake on Baseline 18F-FDG Positron Emission Tomography in Diffuse Large B Cell Lymphoma

Abstract: BM uptake in pretreatment F-FDG PET/CT is an important prognostic factor in DLBCL patients. Moreover, in consideration of high NPV,F-FDG PET/CT could eliminate unnecessary BMB in FDG-negative patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The finding of dPET+ of BM is not rare in DLBCL. In some studies, this kind of BM pattern was interpreted negative for BMI 2 , while some other researchers considered it as positive 11 , 19 , 20 . The disagreement on the interpretation made it difficult to accurately assess the value of dPET+ in DLBCL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding of dPET+ of BM is not rare in DLBCL. In some studies, this kind of BM pattern was interpreted negative for BMI 2 , while some other researchers considered it as positive 11 , 19 , 20 . The disagreement on the interpretation made it difficult to accurately assess the value of dPET+ in DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of BMI based on FDG PET/CT is still not demonstrated clearly. Some studies indicated the excellent prognostic value of PET-BMI in DLBCL patients 2 , 11 , 13 , 22 , while some studies drew the opposite conclusion 14 , 19 , 20 . In their studies, the diffuse BM pattern was interpreted differently, thus more or less leading to different conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular imaging provides early-response assessment 208 , chemotherapy monitoring 209 , as well as prognostic insight 210 ; for these purposes, to date, no agent has rivalled the importance and ubiquity of FDG.…”
Section: Imaging and Chemotherapymentioning
confidence: 99%
“…In recent years, positron emission tomography/computed tomography (PET/CT) has become an effective method in the diagnosis and staging of lymphoma [13]. In recent retrospective studies, the diagnostic and prognostic value of PET/CT to determine BMI remains controversial [14,15].…”
Section: Introductionmentioning
confidence: 99%